Are the Nutrient and Textural Properties of Australian Commercial Infant and Toddler Foods Consistent with Infant Feeding Advice?. (29th May 2020) - Moumin, Najma; Green, Tim; Golley, Rebecca; Netting, Merryn
Abstract: Objectives: Australian Infant Feeding Guidelines recommend first foods be iron rich with no added sugars and that nutrient poor discretionary foods be avoided. They also encourage exposing infants to a variety of foods and flavours with increasingly complex textures. Here, we compare nutritional and textural properties of commercially available infant and toddler foods with established guidelines. Methods: Infant and toddler food products available as of August 2019 were identified by searching for 'baby food' on retailer websites and by location in the 'baby food' section of major supermarket chains (Coles, Woolworths, Aldi and Foodland) in Adelaide, South Australia. Manufacturer websites were cross checked to identify all available products. Nutrient composition of foods was obtained from the nutrient information panel on the product label, manufacturer or retailer websites. In total, 446 products from 17 brands were reviewed, which accounted for over 90% of the market share. Results: Most products were poor sources of iron, and 80% of first foods were fruit-based. Half of all products were purees in squeeze pouches and one third of all products were discretionary foods. The nutritional content of many products was inconsistent with guidelines, being low in iron, sweet, smooth in consistency, or classified as discretionary. Conclusions: Reformulation of products is warranted to improve iron content, particularly in mixed main dishes, expand the range of vegetable only foods, and textural variety. Greater regulatory oversight and front of package labelling are needed to better inform parents and caregivers. Frequent consumption of commercial baby foods low in iron may increase risk of iron deficiency. Excessive consumption of purees via squeeze pouches may also have implications for overweight and obesity risk. Funding Sources: There are no funding sources to declare for this research.